SEMANTIC DIFFERENTIAL MODIFICATION FOR PERSONAL IDENTITY INVESTIGATION AMONG STUDENTS - Павленко, Валентина Миколаївна; Джаббарова, Лілія Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article suggests the improvement of a set of concepts for investigations and personal identity analysis. There were selected the concepts: «Integrated personal identity», «Temporal identity», «Spatially active identity», «Stage of consolidation», identity, a method for their operationalization and interpretation is proposed. The article described modifiation of semantic differential method for personal identity studying. We presented and analyzed results on empirical investigation of personal identity among students which was based on suggested modifiation. The similarity of the structure of personal identity types is detected. The stage of temporal identity consolidation is less in comparison with spatially active identity.